2006
DOI: 10.1097/01.bot.0000189881.75421.92
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Posttraumatic Anterior Dislocation of the Radial Head in Children

Abstract: This surgical procedure provides a high success rate with a low level of complications for chronic radial head dislocations in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…So we do not have a homogeneous group of patients, and the number of the patients in each group of our cohort is insufficiently large to be considered significant from the statistical point of view. In the orthopaedic literature, several reports have included more than ten cases [ [10,20,23,[24][25][26][27][28] ], but only Hory and Nakamura more than 15 and few of them provided statistical evidence to support their indication [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…So we do not have a homogeneous group of patients, and the number of the patients in each group of our cohort is insufficiently large to be considered significant from the statistical point of view. In the orthopaedic literature, several reports have included more than ten cases [ [10,20,23,[24][25][26][27][28] ], but only Hory and Nakamura more than 15 and few of them provided statistical evidence to support their indication [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have done ligament reconstruction in every case whereas others have reported its use only when there is residual instability of the radial head after ulna osteotomy 78. Annular ligament reconstruction is not without complications and hence its use in every case may not be required 4913…”
Section: Introductionmentioning
confidence: 99%
“…However, in some previous studies, ulnar osteotomy for the treatment of missed Monteggia fracture has been performed at proximal area not original fracture site of the ulnar, which helped maintain the integrity of the interosseous membrane 123233. Although ulnar osteotomy is not a difficult procedure, there are several complications related to ulnar osteotomy, including delayed union, nonunion, fixation failure, and negative cosmetic problems 9143435. Therefore, we think that open reduction of radiocapitellar joint may be considered as first step if the ulnar length and alignment is not deformed severely.…”
Section: Discussionmentioning
confidence: 99%
“…5). The osteotomy site was the area of maximum deformity or at the proximal third of ulna if there was no apparent deformity 1214. After osteotomy, the osteotomy site was angulated to correct the deformity, and the radial head was easily reduced by manipulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation